Numerical Linear Algebra - Pavel Čížek; Lenka Čížková (Humboldt-Universität zu Berlin, Center for Applied Statistics and Economics (CASE), 2004)
Many methods of computational statistics lead to matrix-algebra or numerical- mathematics problems. For example, the least squares method in linear regression reduces to solving a system of linear equations. The principal components method is based on finding eigenvalues and eigenvectors of a matrix. Nonlinear optimization methods such as Newton?s method often employ the inversion of a Hessian matrix. In all these cases, we need numerical linear algebra.
Keywords: 330